Three-dimensional evaluation of hyoid bone position in nasal and mouth breathing subjects with skeletal Class I, and Class II - Amin S. Mohamed; Janvier Habumugisha; Bo Cheng; Minyue Zhao; Yucheng Guo; Rui Zou; Fei Wang (BMC, 2022)
Abstract Background This retrospective study investigated the effect of breathing pattern, skeletal class (Class I, Class II), and age on the hyoid bone position (HBP) in normodivergent subjects. Methods A total of 126 subjects (61 males, 65 females) aged 7-9 years and 10-12 years were scanned using cone-beam computed tomography (CBCT). All participants were classified according to the anteroposterior skeletal pattern into (Class I, Class II). Each skeletal group was further divided according to the breathing mode into mouth breathers (MB) and nasal breathers (NB). The HBP was measured accordingly. Independent sample t-test and Mann Whitney U test were used to detect significant differences between the groups, and binary logistic regression was used to identify MB predictive indicators. Results The breathing mode and skeletal class affected the vertical HBP in subjects with 7-9 years, while they affected the anteroposterior HBP in subjects with 10-12 years. Regarding the age effect, hyoid bone was located more anteriorly in the older NB subjects, and hyoid bone was more inferiorly in the older age group. A regression equation of the significant variables was formulated, C3-Me (P: 001, OR: 2.27), and H-EB (P: 0.046, OR: 1.16) were positively correlated with occurrence of MB. Conclusion There were significantly different HBPs among subjects with different anteroposterior skeletal classes, breathing modes, and age cohorts. Moreover, C3-Me, and H-EB were significant predictors and correlated with increased likelihood of being MB subject.